A study on the impact of the first federal funds interest rate hike since the global financial crisis on market expectations and risk preferences - Belo, Rafael Carmona (2017)
This empirical study analyses the impact of the first federal funds interest rate hike since the last global financial crisis. Using a mixture of lognormal, generalised beta of the second kind and lognormal-polynomial distributions, it is estimated risk-neutral densities on S&P 500 options. The mixture of lognormal presents the best fit. Descriptive statistics are used to make comparisons, which shows a decrease in the means of the distributions and an increase in uncertainty after the event. It is estimated the representative investor’s constant relative risk aversion using a power-utility function on expected utility and rank-dependent expected utility models, and it is found a positive risk premium for the year of 2015.